2019
DOI: 10.1016/j.physrep.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in modeling and simulation of nanofluid flows-Part I: Fundamentals and theory

Abstract: It has been more than two decades since the discovery of nanofluids-mixtures of common liquids and solid nanoparticles less than 100 nm in size. As a type of colloidal suspension, nanofluids are typically employed as heat transfer fluids due to their favorable thermal and fluid properties. There have been numerous numerical studies of nanofluids in recent years (more than 1000 in both 2016 and 2017, based on Scopus statistics). Due to the small size and large numbers of nanoparticles that interact with the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
233
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 775 publications
(238 citation statements)
references
References 219 publications
1
233
0
4
Order By: Relevance
“…The exergy loss by the coolant is given by Exf=QTotrue[mfcp,flnTf,iTf,emfpf/(ρfTf,italicmean)true],whereas the exergy gain rate by air is calculated by ΔExa=QTotrue[macp,alntrue(Ta,eTa,itrue)maRnormallnormalntrue(pa,ipa,etrue)true].…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The exergy loss by the coolant is given by Exf=QTotrue[mfcp,flnTf,iTf,emfpf/(ρfTf,italicmean)true],whereas the exergy gain rate by air is calculated by ΔExa=QTotrue[macp,alntrue(Ta,eTa,itrue)maRnormallnormalntrue(pa,ipa,etrue)true].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Nanofluids are a colloidal mixture of nanometer size particle less than 100 nm because all physical bulk solids have a critical length, below which the properties of the bulk solid changes into ordinary fluids to improve the thermal conductivity value and convective heat transfer performance of the base fluid . The dispersion of nanoparticles in the base fluidnot only contirbutes to the increment of thermal conductivity but also increases the heat transfer surface area due to which the convective heat transfer coefficient the heat transfer imrpove . Many researchers have studied the performance of radiators using nanofluids as coolants theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The overall aim of using nanofluids is to have optimum thermophysical properties at minimum particle volume fractions. Moreover, it has been reported that the thermal conductivity of nanofluids increases with the increase of nanoparticle concentration . It has also been revealed that the thermal conductivity enhancement ratio declines with that of the base fluid, while it is directly proportional to the nanoparticle thermal conductivity .…”
Section: Introductionmentioning
confidence: 97%
“…From the above review, it can be noticed that all the different parameters and mechanisms affecting the thermal conductivity of nanofluids cannot be accounted by the traditional models of particle suspensions . Thus, several models have been proposed, such as the work of Alrashed et al using an enhanced artificial neural network (EANN) and an adaptive neuro‐fuzzy inference system approach and the results showed a suitable accuracy with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the aforementioned shortages of a SBPTSC, a direct‐absorption solar collector (DASC) can be adopted as been widely used in the low temperature regime . In a DASC, the nanoparticles dispersed in the nanofluids directly interact and absorb the solar energy; thus, the absorber coating is no longer needed.…”
Section: Introductionmentioning
confidence: 99%